Evaluation of autonomic nervous system function in children with overactive bladder syndrome. Issue 3 (21st March 2016) - Demir, Aysegul Dogan; Gursoy, Azize Esra; Goknar, Nilufer; Uzuner, Selcuk; Ozkaya, Emin; Erenberk, Ufuk; Vehapoglu, Aysel; Dundaroz, Mehmet Rusen; Oktem, Faruk
Abstract : Purpose: We aimed to evaluate the autonomic nervous system activity in children with overactive bladder (OAB) syndrome. Methods: Included in the study were 40 children with overactive bladder and 28 healthy controls. Autonomic tests were performed on all participants, including heart rate interval variation ( RRIV), heart rate response to valsalva maneuver, and sympathetic skin response (SSR). Results: Mean valsalva rates in the overactive bladder and control groups were 1.53 ± 0.29 and 1.30 ± 0.18, respectively, a statistically significant difference ( P < 0.001). Also significantly different were deep breathing RRIV values of the study and control groups: 56.65 ± 14.66 and 47.92 ± 10.15, respectively ( P = 0.008). No statistical differences were found in SSR when OAB patients were compared with controls ( P > 0.05). Conclusions: This study demonstrated a parasympathetic hyperactivity in children with OAB, results suggesting a dysfunction in their autonomic nervous systems. Neurourol. Urodynam. 36:673–676, 2017 . © 2016 Wiley Periodicals, Inc.